The elements and characteristics of folklore among the Batek Tribe in Taman Negara Pahang Darul Makmur, Malaysia / Noreha Taib … [et al.] - Taib, Noreha; Wan Ariffin, Wan Latifah; Manap, Mohammad Radzi; Mohd Kasim, Aini Akmar; Mohamed Jais, Ismie Roha; Abd. Wahab, Azhar; Abdul Latif, Mohd Sofian (2009)
This research aims to document the folklore of the Batek Tribe in Taman Negara, Pahang Darul Makmur, Malaysia as part of the initiative to preserve the national heritage of Malaysia. It also seeks to identify the main characters and the common elements and characteristics found in the Batek folklore. The Batek tribe was selected for the study as very little investigation has been carried out on its folklore. The fieldwork was carried out at four Batek settlement areas in Pahang. Semi-structured interviews and observations were used to collect data. Nine Batek folklore/stories were recorded and transcribed during the study. The analysis of the folklore/stories is categorized into the common elements, characters and characteristics found in them. The Cohen Kappa inter-rater agreement indicated almost perfect agreement of the element codes achieved by the rater. Most of the elements and characteristics found in Batek folklore are similar to those identified in Bassett's manual. It was found that the protagonists are the youngest son in a family. Bongsu (literally meaning youngest) is depicted as intelligent, brave, dependable and the person who solves the problems usually started by the elder brother. The female characters do not play a very significant role in the stories but they are revered for their beauty. There are a lot of supernatural elements found in the stories. The animal characters on the other hand have the ability to communicate like humans. From the stories, we can get a glimpse of the Batek people's belief and practices in the past. As more and more of the Batek people embrace Islam, their beliefs, culture and practices go through the process of assimilation. The stories, if they are not documented will also undergo changes if they were to remain in its oral form.